‘To Form a New Compound’: Eliot, Bergson, and Cubism - Shun-liang Chao (Études Britanniques Contemporaines, 2006)
This paper seeks to elaborate on the less discussed connection between Eliot’s poetics and Cubist aesthetics in terms of Bergson’s theory of durée. The idea of ‘a new compound’ is a theme common to Eliot’s poetic theory and Cubist aesthetics. The poet’s ability to fuse disparate elements into a new whole is a thread running through the fabric of Eliot’s poetics: his idea of tradition, of unified sensibility, of impersonal theory of poetry, and so forth. One can find that underlying Eliot’s notion of moulding a new compound is Bergson’s conception of durée as the inter-penetration of diverse inner states. Bergson’s theory of durée enables Cubist painters to have a new view of reality and thereby create the ‘multiple viewpoints’ technique—which brings to Cubist canvases ‘the Fourth Dimension’—to fashion new wholes.